UNDERSTANDING THE CONSTRUCT "DESIRE" IN THE PERSONALITY STRUCTURE ACCORDING TO THE METHOD OF PSYCHOTHERAPY "SELF -RECONSTRUCTION" - Pavlenko, Tetiana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article analyzes the concept of personality structure in the method, and substantiates the necessity of this component in the direction of research. The concept of "construct" is defined, as it is key in the development of the components of the personality structure according to the "Self-reconstruction" method of psychotherapy. The main approaches to defining the construct "desire" were analyzed and the author’s definition of its phenomenon was developed. The theoretical materials are illustrated with appropriate tables. The purpose of the study is to highlight the views on the role of the "desire" construct in the formation of personal injuries and their impact on life. Research methods: theoretical analysis, scientific works in the field of psychology, medicine; systematization and logical generalization of the received material. The research procedure involved the use of bibliographic, step-by-step problem-solving and comparative methods in order to understand the construct of "desire" in the personality structure according to the " Self - reconstruction" method of psychotherapy. It was determined that in order to develop the personality structure, it is necessary to take into account a number of compliance criteria that will allow to fully reflect the internal processes. According to these criteria, a completely new personality structure was proposed and the concept of "personal construct" was clarified. The main constructs according to the " Self -reconstruction" method of psychotherapy are desire, possession and satisfaction, the interaction and manifestation of which are reflected in the author’s model. It turned out that in psychological and philosophical literature, desire is perceived more as a cause of difficulties, urges that bring difficulties rather than relief. As a result, the author’s definition of the construct "desire" was proposed, and the trauma formation of this construct was illustrated according to the method of psychotherapy " Self -reconstruction". The conclusions summarized the role of the "desire" construct in reflecting the personality structure, and showed the possibilities of working in it, in the psychotherapeutic process. For example, fear, anxiety, anger during the construction of the request, the inability to clearly form an idea about the final result of the work, I am one of the signs of traumatization of this construct.